Hyperpolarized 13C NMR observation of lactate kinetics in skeletal muscle - Park, J. M.; Josan, J.; Mayer, D.; Hurd, R. E.; Chung, Y.; Bendahan, D.; Spielman, D. M.; Jue, T. (The Journal of Experimental Biology, 2015)
The production of glycolytic end products, such as lactate, usually evokes a cellular shift from aerobic to anaerobic ATP generation and O2 insufficiency. In the classical view, muscle lactate must be exported to the liver for clearance. However, lactate also forms under well-oxygenated conditions, and this has led investigators to postulate lactate shuttling from non-oxidative to oxidative muscle fiber, where it can serve as a precursor. Indeed, the intracellular lactate shuttle and the glycogen shunt hypotheses expand the vision to include a dynamic mobilization and utilization of lactate during a muscle contraction cycle. Testing the tenability of these provocative ideas during a rapid contraction cycle has posed a technical challenge. The present study reports the use of hyperpolarized [1-13C]lactate and [2-13C]pyruvate in dynamic nuclear polarization (DNP) NMR experiments to measure the rapid pyruvate and lactate kinetics in rat muscle. With a 3 s temporal resolution, 13C DNP NMR detects both [1-13C]lactate and [2-13C]pyruvate kinetics in muscle. Infusion of dichloroacetate stimulates pyruvate dehydrogenase activity and shifts the kinetics toward oxidative metabolism. Bicarbonate formation from [1-13C]lactate increases sharply and acetyl-l-carnitine, acetoacetate and glutamate levels also rise. Such a quick mobilization of pyruvate and lactate toward oxidative metabolism supports the postulated role of lactate in the glycogen shunt and the intracellular lactate shuttle models. The study thus introduces an innovative DNP approach to measure metabolite transients, which will help delineate the cellular and physiological role of lactate and glycolytic end products.